Nurses Opinions about the Transformational Leadership in Hospitals of Pune City - Merlin Suji1 , Poonam Yadav1 , Seeta Devi2, Manisha Mistry2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Transformational leadership in nursing is different from other industries. Nurses working pattern is differentwith different shift and many times they go through a lot of emotional changes with the patient care. Effectivenursing leadership also engenders staff retention, job satisfaction, commitment, work unit climate and clientsatisfaction with the nursing care services provided to them .Transformational leadership globally plays avital role in the health care system especially for patient care by nurses, because the performance of thestaff nurses is directly linked to the leadership styles. Hence this study is aimed to assess the of nurses ontransformational leadership styleMethodology: ANon-Experimental Descriptive Research approach used. The study was conducted amongvarious Hospitals of Pune City. The selection of the sample was based on easy geographical accessibility,cooperation and availability of samples .The sample size for the study was 95,selected by using nonprobability convenience sampling technique from various Hospitals of Pune City who met the inclusioncriteria. A structured modified questionnaire was developed based on the research problem, to get theinformation from the samples.Result: The result of current study says 54.74%staff nurses given the opinion that their nurse supervisors arehaving average transformational leadership. 38.95% of staff nurses perception was their nurse supervisorsare having good transformational leadership and 6. 32 % of staff nurses perception was their nurse managersare having poor transformational leadership qualities.The average score of staff nurses regarding theirsupervisor’s transformational leadership is 3.1 to 4.2. Out of the four domains Individualism got higherpoints (79.72%) than other and improvements of subordinates got the lowest ( 64.65%).Conclusion: The nursing leader transformational qualities in four main domain is analysed in this study.The overall competencies in nurse leaders analysed were knowledge, innovativeness, self-confidence, goodcommunication skill, adaptability, teamwork, organisational skill etc. The result says that nurse managersare having average transformational leadership qualities.